STRATEGI KOMUNIKASI HUMAS POLSEK KEBAYORAN LAMA MELAUI TWO-WAY SYMMETRICAL COMMUNICATION (EDUKASI TENTANG KEAMANAN) - Hadiani, Pemi Nur; Romadhan, Mohammad Insan; Rizqi, Muchamad (Sintesa, 2024)
The increasing crime / crime in Indonesia, especially in several areas of Jakarta, the public is urged to always be vigilant. A crime that is rife today in the Kebayoran Lama area is motorcycle theft. Theft is a criminal act committed by a person or group to take other people’s property illegally or without the permission of the owner. Due to the increase in motorcycle theft, there is a responsibility of the police to provide social awareness through socialization activities and educate the public to be more vigilant. It is very necessary to immediately carry out security education by communicating with the community to provide direction, guidance and solutions to maintain security independently as a form of prevention and minimize crime around. Thus, there is a role for the Police in community life to create good cooperation with the community. The writing method used is qualitative-descriptive and this writing consists of primary and secondary data sources. The results showed that Police Public Relations in carrying out a two-way symmetrical communication strategy through several characteristics of the PR model, namely: 1) Mutual understanding, 2) Balanced effect, 3) Person to person, 4) Evaluation. Furthermore, the PR management process, namely: 1) Defining PR Problems, 2) Planning and Programming, 3) Taking Action and Communicating, 4) Evaluating Programs. It can also be concluded that the activities carried out by the Police Public Relations do not move alone, but work together with various other divisions to succeed their vision and mission. One of the key factors for the success of the Polsek Public Relations communication strategy can be received by the community and a positive response from the community with the information conveyed, community approaches through dialogue and social activities, as well as program activities carried out by collaborating, and publicizing every activity carried out by the Kebayoran Lama Police through several owned media so as to make it easier for the public to widely know and receive information related to security appeals and crimes around it. Keywords: Communication Strategy; Public relations; Safety Education;The role of the police; Crime